Abordagem da funcionalidade em instrumentos de triagem do desenvolvimento infantil na Atenção Primária à Saúde sob a perspectiva da Classificação Internacional de Funcionalidade, Incapacidade e Saúde - Fonteles, Barbara Helen Lima Farias (2025)
INTRODUCTION: The World Health Organization (WHO), through the International Classification of Functioning, Disability and Health (ICF), recommends that the assessment of a health condition consider, in addition to body functions and structures, life activities, social participation and contextual factors (environmental and personal). Regarding functioning in child development, a critical phase is observed, marked by maturation and acquisition of several skills. OBJECTIVES: To identify the temporal evolution of functioning in child development screening instruments in primary health care and to link the significant concepts of the questions in the instruments with the first and second level classifications of the ICF and to understand the distribution of these categories within the instruments. METHOD: An integrative review was carried out in the Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and PubMed databases. The keywords used were: “Child Development”, “Primary Health Care”, “Functioning”, “Disability”, “Disabilities”. In addition, a methodological study was conducted based on the new instruments selected in the aforementioned review. From these instruments, the linking process was carried out based on Cieza, 200xx. Each question was linked to the ICF components and the first and second level categories. RESULTS: A total of 343 articles were found in the three databases, resulting in 10 studies, from which 9 instruments were extracted. The process of extracting concepts from these nine instruments generated a total of 701 significant concepts, distributed as follows: Body Functions (17.5%), Body Structures (0.71%), Activities and Participation (56.4%), Environmental Factors (13.4%), Personal Factors (9.8%) and Not Covered (1.9%). In the timeline, the articles analyzed cover the period from 2012 to 2022. The PEDS and AHEMD instruments did not present items linked to the body level. The category "Functions of the skin and related structures" (Chapter 8 of the ICF) was the only first-level category not linked to the instruments at the body level. All activity levels were addressed in the instruments, but the PEDS instruments and the IMCI manual do not assess the social level. The first-level classifications "Communication" (Chapter 3 of the ICF) and "Personal care" (Chapter 5 of the ICF) were not found within the instruments at the social level. Furthermore, the AIMS and Denver II instruments do not assess Environmental Factors, and the category "Services, systems and policies" was the only first-level category not identified. CONCLUSION: Although the ICF was created in 2001, most of the articles presenting instruments aligned with the biopsychosocial perspective were published in the last decade. None of the instruments applied covers all the components proposed by the ICF. However, when relating their concepts to the ICF, there was a greater presence of the activity and participation component in the instruments. With a more heterogeneous distribution of components among the instruments, a combination of different instruments is suggested to ensure a comprehensive assessment of the child, such as the association of the SWYC instrument with the AHEMD.